Evidence of climate change impact upon glaciers’ recession within the Italian Alps: the case of Lombardy glaciers - G. Diolaiuti; D. Bocchiola; C. D’Agata; C. Smiraglia (Theoretical and Applied Climatology, 2012)
We analyze a daily series of rainfall, snowfall, air temperature, and snow water equivalent at fixed dates from 40 high-altitude stations on the Adamello Glacier area (Italian Alps), for the period 1965–2007. Purposes of the study are (1) to investigate significant variation in time, (2) to evaluate effect of temperature changes on cryospheric water cycle, and (3) to evaluate underlying climate patterns and the most significant variables for climate change studies. We detect the presence of a trend using linear regression, moving window average and Mann Kendall test. Linear dependence of water related variables on temperatures is assessed. We find substantially unchanged atmospheric water input along with increasing temperature and rainfall, decreasing snowfall and snow water equivalent at thaw, and shortening of snow cover extent and duration. We carry out a principal components analysis which highlights patterns of precipitation distribution resulting from local temperature and external forcing. A set of the most representative variables for climate and glacier studies is then assessed. A comparison with three nearby Southern Alpine glacierized areas in Italy and Switzerland shows substantial agreement. In spite of the relative shortness of the series, the results here are of interest and can be used as a benchmark for climate change impact assessment for the Adamello Glacier area and southern Alps.